2020
DOI: 10.1016/j.ijscr.2020.06.078
|View full text |Cite
|
Sign up to set email alerts
|

Robotic management of painful Zinner syndrome, case report and review of literature

Abstract: Highlights Zinner Syndrome is a congenital pathology due to an embryologic anomaly. This embryologic defect leads to unilateral renal agenesis, ipsilateral seminal vesicle cyst and ejaculatory duct obstruction. Complete excision of the seminal vesicle cyst is the only 100% effective treatment option for symptomatic patients. Minimally invasive approach like laparoscopy or robotic assisted laparoscopy should be considered as the surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Likewise, Demaeyer et al decided to use a robotic-assisted approach to completely remove the cyst and the right seminal vesicle of a 33-year-old man with symptomatic Zinner’s syndrome. They suggested that minimally invasive approaches, similar to conventional and robotic-assisted laparoscopy, should be considered the gold standard surgical treatments for this condition, given their safety and effectiveness [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Demaeyer et al decided to use a robotic-assisted approach to completely remove the cyst and the right seminal vesicle of a 33-year-old man with symptomatic Zinner’s syndrome. They suggested that minimally invasive approaches, similar to conventional and robotic-assisted laparoscopy, should be considered the gold standard surgical treatments for this condition, given their safety and effectiveness [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Open surgery, performed through a transvesical, retrovesical, transperineal, or transcoccygeal approach, was historically the first treatment modality that was associated with a high success rate. Nowadays, transurethral, laparoscopic, and robotic-assisted approaches are also performed to treat Zinner’s syndrome [ 5 , 6 ]. Abdominal ultrasound can provide information about the composition, dimensions, and exact location of a mass; the bladder’s integrity; and the presence of ipsilateral renal agenesis or dysgenesis.…”
Section: Introductionmentioning
confidence: 99%
“…According to Demaeyer et al, we keep in mind its potential relapse. So this method is suitable but probably shouldn’t be repeated if the desired results are not achieved [ 9 ]. The authors agree that only the surgical excision of the cyst and seminal vesicle is 100% effective.…”
Section: Discussionmentioning
confidence: 99%
“…Less invasive procedures such as conventional laparoscopic surgeries are now suggested. The latest articles also describe robotic-assisted surgeries, but the combination of the rarity of the disease and the inaccessibility of advanced tools such as a robot everywhere results in less than 10 cases described in the literature [ 9 ]. Unfortunately, there is no consensus on the best treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of open, laparoscopic, and robotically assisted excision of the cysts [4,5], and the patients have all experienced a resolution of their symptoms after treatment. Aspiration of symptomatic cysts, however, tends to lead to recurrence of the symptoms, ultimately requiring surgical excision at a later date [6][7][8]. In patients where infertility was the presenting complaint, transurethral resection of the ejaculatory ducts was attempted [9], with subsequent improvement in semen characteristics.…”
mentioning
confidence: 99%